Botulinum toxin therapy in Frey's syndrome: a retrospective study of 440 treatments in 100 patients. (29th August 2016) - Jansen, S.; Jerowski, M.; Ludwig, L.; Fischer‐Krall, E.; Beutner, D.; Grosheva, M.
Abstract : Objective: Frey's syndrome is characterised as sweating, redness and warmth of the parotideal area and is often treated with botulinum toxin A. The objective of this retrospective study was to prove whether the toxin dosage and time‐to‐treatment intervals change after repeated botulinum toxin injections. Study design/methods: The charts of patients, who were treated for Frey′s syndrome during the last 16 years, were assessed. Three brands of botulinum toxin A were available for therapy. The Minor test was used to confirm the sweating before each treatment and to determine the toxin dosage. Constant amount of botulinum toxin was injected per cm 2 of the affected area. Patients consulted our department for the next treatment as soon as they felt disturbed by recurring sweating and when the sweating was objectively evident in the Minor test. Time intervals between treatments and injected toxin dosages were assessed. Results: In total, 100 patients received 440 treatments in 16 years. Repeated injections, median 4.0, were carried out in 70.5% of patients. Median time interval to the first injection was 2.8 years. Median time interval between treatments was 12.0 months and showed to be steady (anova, P = .49, F = 1.01). Conclusion: Duration of effect of botulinum toxin on Frey's syndrome was long‐lasting and stable with no significantly different time intervals between treatments. The extent of the sweating area did not vary significantly after repeated treatments and required a constant dose of botulinum toxin A.